PENGARUH KARAKTERISTIK INTERNAL DAN EKSTERNAL PERILAKU PROFESIONALISME AUDITOR TERHADAP PREMATURE SIGN OFF (STUDI EMPIRIS PADA BPK-RI REGIONAL JAWA TENGAH) (Students' Journal of Accounting and Banking, 2015)
This study examines the effect of time pressure, audit risk, materiality, locus of control, and professional commitment to the premature sign off. This research was conducted at the BPK-RI Regional Jawa Tengah. The sampling method using convenience sampling, and acquired 75 respondents. Influence the relationship between variables described by multiple regression analysis method. The results showed that there were significant differences on the order of priority audit procedures. Variable audit risk and locus of control have significant positive effect on premature sign off, and variable materiality and professional commitment have significant negative effect on premature sign off. While time pressure has no significant effect on premature sign off.Keywords: Time Pressure, Audit Risk, Materiality, Locus of Control, Professional Commitment and Premature Sign Off